PURCHASE INTEREST REVIEWED BASED ON PRICE AND LOCATION AT DANU JAYA BIRDSHOP PEMATANG SIANTAR - Efendi, Efendi; Butarbutar, Marisi; Girsang, Rosita Manawari; Chandra, Erbin; Candra, Vivi (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The research objective is to determine the impact of price and location on buying interest. The approach used in the research design is a qualitative descriptive approach and a quantitative descriptive approach. This study uses a test of validity, reliability, normality, simple linear regression, correlation and determination, the t test with the results of the study, namely a positive and significant effect between price and location on buying interest and a moderately high level of relationship. The contribution of price and location to buying interest was 49,5%